Dinamika Interaksi Teman Sebaya: Memahami Dampaknya terhadap Perilaku Bullying - Dony Darma Sagita; Sari Wardani Simarmata; uliya Khoirun Nisa; Apri Kasman (Universitas Sebelas Maret, 2026)
This study examines the relationship between peer interaction and bullying behavior in adolescents, aiming to identify effective strategies to mitigate bullying. Using a quantitative approach, the study employs simple regression analysis to analyze data collected through a Likert scale. The sample comprised 232 adolescents selected through random sampling. Results indicate that peer interaction exerts a significant negative effect on bullying behavior, as evidenced by a regression coefficient of -0.412. This finding suggests that enhancing positive peer interactions may reduce bullying behavior by 0.412 units. The study recommends that schools implement intervention programs fostering cooperation and communication among students and reinforce guidance and counseling services to support adolescents' social and emotional development. In summary, promoting positive peer interactions appears to be an effective approach to reducing bullying behavior among adolescents.